From Demonstration to Anarchy: The October 1968 Surabaya Incident in Newspaper: Dari Demonstrasi Ke Anarki: Peristiwa Surabaya Oktober 1968 Dalam Pemberitaan Surat Kabar - Tiara Paramita; Nugroho Bayu Wijanarko (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The Surabaya Incident of October 1968 was a significant episode in the early New Order period that began with youth and student demonstrations protesting the execution of two Indonesian Marine Corps (KKO-AL) members, Harun and Usman, by the Singapore government. The demonstrations subsequently escalated into widespread unrest, resulting in property destruction, casualties, arrests, and social and economic disruption. This study aims to examine the chronology and impacts of the incident and analyze how Suara Merdeka and Kompas reported and constructed the event through an anti-communist framework. This research employs the historical method, consisting of heuristic, source criticism, interpretation, and historiography, using newspaper reports published between October and November 1968 as primary sources. The findings show that both newspapers initially portrayed the incident as a demonstration that developed into unrest and was subsequently associated with alleged involvement of former G30S/PKI elements and foreign political forces. The reliance on official military sources contributed to strengthening the anti-communist framework used to explain the causes and actors behind the unrest. The novelty of this study lies in analyzing how the Surabaya Incident was gradually reconstructed in newspaper reporting from a local demonstration into part of a broader anti-communist narrative within the political context of the early New Order.